EDUKASI TENTANG PENTINGNYA MENGENAL DAMPAK DAN EFEK SAMPING METFORMIN HCL PADA MAHASISWA - Yuwanda, Alhara; Maulina, Megi; Nopratilova, Nopratilova; Sabila, Ahda; Akbar, Rayhan (Universitas Mataram, 2025)
Metformin HCl is an antidiabetic drug widely used in the management of type 2 diabetes mellitus. Although its effectiveness has been proven, understanding of the impacts and side effects of Metformin HCl remains limited among students, especially those from non-health-related backgrounds. This lack of knowledge can potentially lead to misuse or careless use of the medication. Therefore, this community service activity was carried out with the aim of increasing students' understanding of the risks, side effects, and proper use of Metformin HCl as part of preventive health education. The method used involved educational outreach through simple and engaging posters, along with evaluations conducted via pre-tests and post-tests. The activity involved 20 students from various study programs at Universitas Global Jakarta. The pre-test results showed that 80% of students lacked sufficient understanding of Metformin HCl, including its function, side effects, and usage. This indicates a low level of health literacy among students, particularly those from non-health disciplines, regarding this commonly used antidiabetic medication. Following the educational session, there was a significant increase in participants’ level of understanding. The post-test results showed that 100% of students reported understanding the material presented. This improvement indicates the effectiveness of the educational method used in this community service activity. Thus, education has proven to be a strategic step in raising awareness and understanding of rational drug use among students. In conclusion, an interactive educational approach using simple visual media has been proven effective in improving student literacy regarding drug use—specifically Metformin HCl—and in fostering awareness of the importance of managing sugar intake and understanding drug side effects wisely.